Are human rights archives accessible? Challenges and possible solutions to improve access for Dealing with the Past initiatives. Issue 1 (1st August 2021) - Ledauphin, Romain; Josi, Claudia; Siegrist, Rahel
Abstract : Records and archives containing information relating to grave violations of human rights and international humanitarian law represent a fundamental source for, and can become trustworthy documentary evidence within, Dealing with the Past (DWP) processes including truth commissions, criminal tribunals, reparation programs, vetting processes and outreach projects. Those intergovernmental organizations (IGOs) and international non-governmental organizations (INGOs) working in the fields of human rights and peace and security are themselves important observers and actors in DWP processes and hence their records and archives are highly relevant to DWP initiatives. Such organizations should therefore be transparent and be able to facilitate DWP processes by granting access to their records. Given the International Council on Archives' definition of "access" as relating to "… the availability of records for consultation as a result both of legal authorization and the existence of finding aids", and the experience of swisspeace in advising DWP initiatives on collecting evidence and improving records management capacity, swisspeace together with the Swiss Federal Department of Foreign Affairs developed a roadmap which centres on the development of an "archives accessibility maturity model". This tool will not only improve hands-on access in practice, but will ultimately improve knowledge about the multi-layered complexity of archives' accessibility, strengthening the capacity of IGOs, INGOs and DWP initiatives to design and implement their access regulations, and thereby improving DWP initiatives' ability to make successful access requests.